Estudo da resistência à corrosão do aço inoxidável austenítico QN1803 em ambientes com alto teor de cloreto - Linhares, Bruno Gomes (2024)
Stainless steels play a fundamental role in various sectors, from everyday products to industrial and construction components, due to their hardness, ductility, and corrosion resistance properties. The austenitic class is the most popular due to its adaptability to corrosive environments, which is attributed to the chromium and nickel content in their composition. However, the increased consumption of nickel, particularly in stainless steels manufacturing and the production of batteries for electric automobiles, is affecting a shortage of this resource and raising the acquisition price. This scenario, along with the potential health risks associated with direct contact with nickel, is driving the search for new austenitic stainless steels with lower nickel content while preserving or enhancing the properties of traditional ones, such as UNS S30400 and UNS S31600. To support this demand, the austenitic stainless steel QN1803 was developed with reduced nickel content, compensated by higher manganese and nitrogen content, preserving the stability of the austenitic phase, affected by nickel reduction. This material offers enhanced mechanical strength and reduced production costs compared to conventional austenitic stainless steels. Nevertheless, there is still limited information in the literature regarding its electrochemical behavior. Therefore, this study aims to assess the corrosion resistance of QN1803 steel as exposed to circumstances with high chloride content. The methodology includes electrochemical techniques such as open circuit potential (OCP), linear potentiodynamic polarization, chronoamperometry, critical pitting temperature (CPT), electrochemical impedance spectroscopy (EIS), and Mott-Schottky capacitance, all performed in a 2 M NaCl solution; pitting corrosion resistance analysis following ASTM G48-A standards; and mechanical and microstructural characterization by optical microscopy (OM), scanning electron microscopy (SEM) and Rockwell B hardness. These tests were also conducted with UNS S30400 and UNS S31600 steels for performance comparison with QN1803. To conclude, the results indicate that QN1803 austenitic stainless steel is a viable and promising alternative to UNS S30400 and UNS S31600 steels. Its ability to form a stable and resistant passive film, combined with a lower propensity for localized corrosion, ensures significant durability and service life for metallic components in aggressive environments with high salinity.